Pengolahan semula teks lama: Perbandingan strategi penulis wanita Melayu dan wanita barat - Ruzy Suliza Hashim, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
As a discipline, comparative literature invites comparative studies based on the aspects of influence, theme, interdiscipline, and translation which highlight the points of convergence and divergence of one national literature with another. In this article, I appropriate the approach used by Susan Bassnett (1993) in her analysis of gender in English literature. By comparing Malay women writers, Zaihasra and Siti Zainon Ismail, with Western women writers, Angela Carter and Anne Sexton, all of whom use the revisionist strategy in their creative writings, I highlight the intercultural practices of creative productions which reveal the variations of norms and customs of the East and West